Matoš i postmoderna, A.G.M. kao matrix hrvatske književnosti - Rem, Goran (Wydawnictwo Nauka i Innowacje, 2014)
The article Matoš and Croatian Postmodernism shows that it was Boro Pavlović (1921– –2001), the anticipator and „the father” of Croatian postmodernism, the author of fifty collections of poems and numerous media creations of Walter Benjaminʼs provenance in the 50ʼs (exhibition of poems Wein 1942, collection News in 1954, the project-exhibition Encyclopedia poeticain 1957/1958, and computer poem MOrpheusin 1978), who figuratively, impressively, but accurately summed up the importance of the impressionist, symbolist and Art Nouveau author A.G.M. for the overall Croatian literature.
Antun Gustav Matoš and Croatian Postmodernism
Keywords: postmodernism; expressionism; dadaism; surrealism; futurism; constructivism; existentialism